Peningkatan Keterampilan Proses Sains Peserta Didik Melalui Model Pembelajaran Discovery Learning pada Materi Keanekaragaman Hayati - Saleh Nurain; Ani M. Hasan; Marini S. Hamidun (Jurnal Penelitian Pendidikan IPA, 2023)
Research aims to improve students' science process skills by using the Discovery Learning learning model on biodiversity material. This classroom action research was carried out at SMA Negeri 1 Gorontalo. The instruments used in this research were observation sheets and written tests to measure students' science process skills. The research results show that using the discovery learning model can improve students' science process skills. This is proven by the results of the 6 indicators of science process skills, namely observing, classifying/grouping, interpreting, asking questions, hypothesizing and applying the concepts measured, getting an average percentage in cycle I of 70.42% and in cycle II amounting to 81.37%. with an N-Gain score obtained of 0.59 or a value of 0.3 â‰¤ g â‰¤ 0.7 (medium category). The achievement of student learning outcomes as measured by objective test questions also saw an increase in the average score in cycle I of 55% and in cycle II of 76%. Thus it can be concluded that the discovery learning learning model can be used in the learning process which can improve students' science process skills at SMA Negeri 1 Gorontalo and as information material, especially in the use of appropriate learning models in learning activities